Molecular structure-associated pharmacodynamic investigation on benzoyl peroxide using spectroscopic and quantum computational tools. Issue 1 (2nd January 2018) - Aarthi, R.; Ramalingam, S.; Periandy, S.; Senthil Kannan, K.
ABSTRACT: The pharmacodynamic activity on the organic structure of benzoyl peroxide has been analysed by molecular spectroscopical tools (IR, Raman, nuclear magnetic resonance and UV–visible). Simultaneously, the results obtained in the experimental process are verified by performing Quantum Gaussian computational calculations with higher-order basis sets. The actual positions of internal compositions and purity of the compound are verified with the observations of fundamental and group frequency of the recorded pattern of the FT-IR and FT-Raman spectra. The chemical environment of different carbons existing in various entities for approving a drug property is keenly identified and distinguished. The energy level degeneracy among different Frontier molecular orbitals is viewed from the orbital overlapping interaction contour. The biological activity of the present compound is emphasized and correlated with the hyperpolarizability profile of the internal coordinate system of a molecular structure arrangement. The involvement of non-bonding molecular orbital for the inducement of drug reactivity is monitored from the observation of cluster electron transitions. The Gibbs energy for chemical reaction with augmented temperature is relatively discussed, and the continuum of chemical reaction is observed.